ANALYSIS OF THE EFFECT OF TAHFIDZ QURAN EDUCATION ON THE DEVELOPMENT OF SELF-ACTUALIZATION IN SANTRI (Case Study at Pondok Baitul Quran Wonogiri) - Adiyani, Rini (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
Education in Islam refers to Al-Tarbiyah, Al-Ta'dib, Al-Ta'lim, these three terms are often used by Al-Tarbiyah, even though this word has many meanings but its basic meaning shows the meaning of growing, developing, nurturing, caring for, manage and maintain it. The goal of Islamic education is none other than the goal that realizes Islamic ideals. The definition of Tahfizh Al-Quran or tahfidz Quran is composed of two words, namely: tahfizh and Al-Quran. Tahfidz means memorizing and can be interpreted as the process of repeating a lesson, either by reading or listening. The definition of tahfiz or tahfidz Al-Qur'an is the process of memorizing the Al-Quran either by reading or listening to it repeatedly until it is memorized so that each verse can be read without looking at the manuscript. Maslow's theory is applied to see the influence of the tahfidz Quran education they receive in Mahad with the development of self-actualization in the form of aspects of creativity, aspects of morality, aspects of self-acceptance, aspects of spontaneity, aspects of problem solving from students in the attitude, life and daily learning of students in the Mahad Baitul Quran Wonogiri, then Maslow's theory which discusses human needs can become a theoretical basis for developing and answering what is thought in this research. Tahfidz Quran education that needs to be considered as an important aspect is the Al-Qur'an Tahfidz Strategy, Al-Qur'an Tahfidz Method, and Tahfidz Al-Qur'an Learning Media. In self-actualization important aspects that will arise in a person are Creativity, Morality, Self-acceptance, Spontanity, and Problem Solving. Tahfidz al-Qur'an education has a significant influence on the development of self-actualization of students